PERTUMBUHAN STEK BATANG TANAMAN BUAH NAGA (Hylocereus costaricensis) DENGAN PEMBERIAN BEBERAPA KONSENTRASI URIN SAPI - Yunanda, Jhon; Yoseva, Sri; ', Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Dragon fruit (Hylocereus costaricensis) is a type of cactus plants are relatively new in Indonesian society . Dragon fruit cultivation in Indonesia can develop properly due to the tropical climate in Indonesia which provide appropriate environmental conditions for dragon fruit to growth. The research was conducted at Experimental Farm Agricultural Faculty University of Riau, Pekanbaru from December 2013 to March 2014. The research used a completely randomized design with four treatments and five replication. Each experimental unit consisted of 3 plants and 2 plants were sampled. The treatment consist of zero cow urine (U0), cow urine 25% concentration (U1), cow urine 50% concentration (U2) and cow urine 75% concentration (U3). Parameters measured were the time appeared shoots, number of shoots, shoot length, root length increase, increase the number of roots, root volume, fresh weight and dry weight of seedlings. The results showed that the difference in cow urine concentrations give a different effect on the growth of the origin of dragon fruit plant propagating cuttings. Cow urine concentrations of 50% tend to give the best effect at the time appeared shoots, number of shoots, root number, root length, root volume, fresh weight and dry weight of dragon fruit plant propagating material. Keywords : Dragon fruit cutting, cow’s urine, growth.